Age of Menarche among Girls at Allahabad, Uttar Pradesh (Indian Internet Journal of Forensic Medicine and Toxicology, 2015)
The age of menarche at which first menstrual bleeding occurs in female is considered as an important indicator of women health and social wellness. The aim of this study was to find out the mean age at menarche among girls and its association with residential and socio-economic status, and dietary habits. This study was conducted on 265 medical and paramedical students at Allahabad, Uttar Pradesh between October and December 2014. The study was retrospectively conducted with the help of structured questionnaires. Data were analysed for association-of-age of menarche with residential and socio-economic status and dietary habits of girls. Mean and standard deviations (S.D.) were determined for each class observation. Z score was used to test for significance. The mean age at menarche was found to be 11.82 ± 1.42 years. Maximum girls (n = 79, 29.81%) achieved their menarche during 12–13 years of age and the least in age group 15–16 years (n = 5, 1.88%). Study revealed decreasing age at menarche as we moved from lower to higher socio economic groups. Vegetarians attained age of menarche later than the non-vegetarian girls.
Keywords: Age at menarche; Secular trends; Socio-economic status; Residential Status; Dietary habits; Allahabad; social wellness